European Yearbook on Human Rights 2019 / edited by Philip Czech [and four others]. - Czech, Philip (Intersentia, 2019)
2018 has been another challenging year for human rights in Europe and globally. International human rights standards, the rule of law and international human rights institutions have come under increasing pressure. The eleventh volume of the European Yearbook on Human Rights discusses the backgrounds of these developments and outlines the potential implications and possible solutions. The backsliding of democracy in Poland and Hungary, the human rights fallout from Brexit and the human rights situations in Chechnya and the Ukraine are mentioned as just a few examples. The Yearbook also includes contributions on all-time classics such as the right to freedom of expression or fair trial and tensions between security and the protection of human rights, as well as more recent developments on the rights of persons with disabilities and the rights of children to be heard in political processes. The European Yearbook on Human Rights brings together renowned scholars, emerging voices and practitioners. Split into parts devoted to recent developments in the European Union, the Council of Europe and the OSCE as well as through reports from the field, the contributions engage with some of the most important human rights issues and developments in Europe. The Yearbook helps to better understand the rich landscape of the European regional human rights system and is intended to stimulate discussions, critical thinking and further research in this field.